Med24 and Mdh2 are required for Drosophila larval salivary gland cell death - Wang, Lei (2010)
The steroid hormone ecdysone triggers the rapid destruction of larval tissues through transcriptional cascades that culminate in rpr and hid expression and caspase activation. Here we show that mutations in Mdh2 and Med24 block caspase cleavage and larval salivary gland cell death. Mdh2 encodes a predicted malate dehydrogenase that localizes to mitochondria. Consistent with this proposed function, Mdh2 mutants have significantly lower levels of ATP and accumulate late-stage citric acid cycle intermediates, suggesting that the cell death defects arise from a deficit in energy production. Med24 encodes a component of the Mediator transcriptional coactivator complex. Unexpectedly, however, expression of the key death regulator genes is normal in Med24 mutant salivary glands. This study identifies novel mechanisms for controlling the destruction of larval tissues during Drosophila metamorphosis and provides new directions for our understanding of steroid-triggered programmed cell death.